Desastres climáticos, género y pobreza (Serie de Webinars NPS Colombia) : Hacia una reducción inclusiva del riesgo de desastres en Bolivia - Escalante, Luis Enrique; Piñeiro, Valeria (Bioversity International and the International Center for Tropical Agriculture, 2023)
On December 6, 2023, took place the third webinar, carried within the framework of the National Policies and Strategies (NPS) initiative in Colombia, in collaboration with the University of the Andes "Climate Disasters, Gender, and Poverty: Towards an Inclusive Reduction of Disaster Risk in Bolivia" During this seminar, Luis Escalante, a researcher at IFPRI, presented the study as part of the course "Policy Analysis Tools using General Equilibrium Models for Colombia" The study, based on social accounting matrices and household surveys, introduced a dynamic computable general equilibrium (CGE) model. The results highlight the negative impact of climate disasters on Bolivia's Gross Domestic Product (GDP), with a contraction of 1.5%. Additionally, an increase in food prices, a decrease in consumption, and an increase in poverty, particularly affecting women, were observed.